ANALISIS INTERPRETASI PESAN MORAL PADA RAGAM TUTUR MA SIHE’I FOLKLORE DARI NEGERI JAPAKEH PIDIE JAYA: KAJIAN SOSIOLINGUISTIK - Nofiana S; Hayatun Rahmi; Zulfa Zainuddin; Aines Shalsabila (Smart Education, 2026)
The folk tale of Ma Sihe'i from Aceh depicts the relationship between a mother and her child, which is full of moral values. Ma Sihe'i, a loving mother, must deal with her child's rebellious behavior. The purpose of this study is to analyze and describe the moral values contained in the story of Sihe'i from Japakeh Pidie Jaya. The method used in this study is qualitative descriptive. The results of this study show that the moral messages emphasized in this story include the importance of respecting parents, maintaining family relationships, demonstrating responsibility as a child, and understanding the consequences of bad behavior. The values of honesty, kindness, justice, tolerance, and responsibility are reflected in this story, making it a reminder to maintain love and respect for parents as a form of noble devotion.